Can traditional bonesetters become trained technicians? Feasibility study among a cohort of Nigerian traditional bonesetters - Ndubuisi Onu Onyemaechi; Ijeoma Uchenna Itanyi; Paulinus Okechukwu Ossai; Echezona Edozie Ezeanolue (BMC, 2020)
Abstract Background Traditional bonesetters (TBS) provide the majority of primary fracture care in Nigeria and other low- and middle-income countries (LMICs). They are widely patronized and their services are commonly associated with complications. The aim of the study was to establish the feasibility of formal training of TBS and subsequent integration into the healthcare system. Methods Two focus group discussions were conducted involving five TBS and eight orthopaedic surgeons in Enugu Nigeria. Audio-recordings made during the focus groups were transcribed verbatim and analysed using a thematic analysis method. Results Four themes were identified: Training of TBS, their experiences and challenges; perception of traditional bonesetting by orthopaedic surgeons; need for formal training TBS and willingness to offer and accept formal training to improve TBS practice. Participants (TBS group) acquired their skills through informal training by apprenticeship from relatives and family members. They recognized the need to formalize their training and were willing to accept training support from orthopaedists. The orthopaedists recognized that the TBS play a vital role in filling the gap created by shortage of orthopaedic surgeons and are willing to provide training support to them. Conclusion This study demonstrates the feasibility of providing formal training to TBS by orthopaedic surgeons to improve the quality of services and outcomes of TBS treatment. This is critical for integration of TBS into the primary healthcare system as orthopaedic technicians. Undoubtedly, this will transform the trauma system in Nigeria and other LMICs where TBS are widely patronized.